Exploring the role of social support as moderator in mitigating the impact of quantitative job demands on burnout among working mothers : A quantitative study - Suri, Shafira Asiva; Radikun, Tulus Budi Sulistyo (International Journal of Research in Counseling and Education, 2023)
Women's participation in the Indonesian labor market reached 48.65% by 2022, indicating an increase over the last decade. Women's participation in the labor market, especially working mothers, raises new challenges, such as long working hours, as they are responsible for caring for household and office work that puts them at risk of burnout. Therefore, the study investigates the role of moderation of social support in the relationship between quantitative demands and burnout among working mothers. The study used a sample of 148 participants in Indonesia with the characteristics of married women employees aged 21-55 who had children and worked at least six months at the company. The work background and company background are not limited to the participant sample. This study used the Oldenburg Burnout Inventory (OLBI) as a burnout measurement tool, the Copenhagen Psychosocial Questionnaire (COPSOQ) as a workplace support and quantitative labor demands measuring tool, and the Family Support Scale as a family support measure. Data analysis using the macro process Hayes model 1 moderation regression in the SPSS program showed that social support has a significant moderation effect of social support on the relationship between quantitative labor demands and burnout in hybrid working mothers or WFH. Hybrid or WFH mothers have a lower risk of burnout when getting higher social support. Therefore, it is important to have support from the workplace, both from the superior and colleagues and from family and close relatives.